New bearings in English studies : a festschrift for C. T. Indra - Azhagarasan, R.; Indra, C. T. Chidambaram Thathachari 1947 (New Delhi : Orient Longman, 2008)
Contributed articles on English literature and language; a few on Indic English literature; commemorative volume on the sixtieth birthday of Chidambaram Thathachari Indra, b. 1947, Indian academician
Includes bibliographical references
Keywords: Postmodernism (Literature); English literature -- History and criticism; English teachers -- India; Globalization in literature; English literature -- Translations; Cosmopolitanism in literature; Transnationalism -- In literature; Caste in literature; Imperialism in literature